Comparison of the effects of supreme laryngeal mask airway and endotracheal tube on airway reflexes in patients who underwent nasal surgery: A randomized, controlled clinical trial (Annals of Medical Research, 2021)
Aim: The primary purpose of this study was to compare the effects of supreme laryngeal mask airway (SLMA) and endotracheal tube (ETT) on (laryngospasm, bronchospasm, cough, desaturation) airway reflexes in patients who undergo nasal surgery. The secondary purpose was to evaluate the hemodynamic responses in this respect.Material and Methods: The study was conducted as a prospective, randomized, single blind and controlled clinical trial in 92 patients between the ages of 18 and 65 for whom elective nasal surgery was planned, who volunteered for the study and who were American Society of Anaesthesiologists (ASA) I-II group. The patients were divided randomly into two groups as the supreme laryngeal mask (SLMA Group, n = 46), and the endotracheal tube (ETT Group, n = 46). The laryngospasm, bronchospasm, cough, desaturation (SpO2 ≤90) and hemodynamic parameters were evaluated after the extubation (T1) 5th and (T2) 60th minutes.Results: The demographic data were similar in both groups. In the SLMA Group, laryngospasm was detected at T1: (5th minute after the extubation) in 2 (4.3%) patients, Bronchospasm was detected at T1 (2.2%) in 1 patient, cough was detected at T1 in 4 (8.7%) patients, desaturation was detected at 3 (6.5%) patients. In the ETT Group, laryngospasm was detected at T1 (13%) in 6 patients (13%), bronchospasm was detected at T1 in 2 patients (4.3%), cough was detected at T1 (10.9%) in 5 patients, desaturation was detected in 5 patients (10.9%). There were no statistically significant differences between the groups in terms of the perioperative respiratory complications. Conclusion: It was determined in our study that the incidence of the respiratory adverse events (laryngospasm, bronchospasm, and cough) in the patients applied SLMA was less than ETT in nasal surgery patients undergoing general anesthesia.
Keywords: Supreme laryngeal mask airway; endotracheal tube; respiratory adverse event.